Populism in Ukrainian political culture - M. M. Rohozha (Ukrainian Cultural Studies, 2020)
The paper deals with populism as the phenomenon of political culture in Ukrainian context. The President Election in Ukraine, 2019, has opened the new page in the development of populism not only in Ukraine, but in the world in general. Before that, no political force had won in such a persuasive way. Political analysis and prognoses, proclaimed before the election, look weak today. The paper outlines that populism is homological to democratic foundations of public life, but hypertrophied and unbalanced. It upraises as the reaction on social crisis and challenge to the stable way of life in the presence of political disturbance in different social segments and is connected with the appearance the political leader who uses specific logics of articulation of messages, the shape and the way of their representations to get and keep the political power. Such messages concern the people, like the appeal to it as to the certain integrity; the immediacy of its perception; the adjustment to its demands; the simplification of its view on the public life up to the black and white tones; the offer of the simple and unambiguous decisions. Populism as the phenomenon of political culture provokes the spectrum of ethical problems. Among them such as: manipulation of concepts of the people’s internal homogeneity, integrity and moral purity; opposition of the "people" and the "elite" in the terms of good and evil; active use of moral demagogy and the practice of opportunism; cohesion of business and the state, corruption, nepotism; destruction of public spirit; activation of ressentiment and so on. Today S. Žižek mentions culturalization of politics, and many scholars outline correlation of processes in culture and arts and in politics. Also they call contemporary form of populism as postmodern populism. Independent Ukraine is very sensitive to populist challenges. Here postmodern populism and its technologies of the games with reality have won the victory. It is not only the source of new political experience. It creates new political culture here and now, that demands from scholars to comprehend these processes in real time mode. Postmodern populism does not leave the hope for catharsis, for social stress relief. Soaked in laughter, contemporary political culture is ridicule, and it destroys the political space. Sense of unreality and futile strengthens the comprehension of the impossibility to change such order of things on the due one.